CONCUR 2012 - Concurrency theory 23rd International Conference, CONCUR 2012, Newcastle upon Tyne, UK, September 4-7, 2012. Proceedings - Ulidowski, Irek; Koutny, Maciej (Lecture notes in computer science, 2012)
This book constitutes the thoroughly refereed proceedings of the 23rd International Conference on Concurrency Theory, CONCUR 2012, held in Newcastle upon Tyne, UK, September 4-7, 2012. The 35 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 97 submissions. The papers are organized in topics such as reachability analysis; qualitative and timed systems; behavioural equivalences; temporal logics; session types; abstraction; mobility and space in process algebras; stochastic systems; probabilistic systems; Petri nets and non-sequential semantics; verification; decidability.